Effects of repetitive transcranial magnetic stimulation over the contralesional dorsal premotor cortex on upper limb function in severe ischaemic stroke: study protocol for a randomised controlled trial - Xi Yang; Yi Zhu; Tong Wang; Ying Shen; Lu Fang; Wenjun Dai; Canhuan Liu; Hongyuan Ding; Chuan Guo; Manyu Dong; Yilun Qian (BMJ Open)
Introduction Repetitive transcranial magnetic stimulation (rTMS) is an evidence-based treatment widely recommended to promote hand motor recovery after ischaemic stroke. However, the therapeutic efficacy of rTMS over the motor cortex in stroke patients is currently restricted and heterogeneous. This study aimed to determine whether excitatory rTMS over the contralesional dorsal premotor cortex (cPMd) facilitates the functional recovery of the upper limbs during the postacute stage of severe ischaemic stroke.Methods and analysis This study will be conducted as a single-blind, controlled, randomised study, in which 44 patients with poststroke hemiplegia with a course of disease ranging from 1 week to 3 months and Fugl-Meyer upper limb score ≤22 will be enrolled. The study participants will be randomly assigned to groups A (n=22) and B (n=22). The two groups are based on routine rehabilitation training and drug treatment; group A will be treated with low-frequency (1 Hz) rTMS over the contralesional primary motor cortex (cM1), and group B will be treated with high-frequency (10 Hz) rTMS over cPMd. For 2 weeks, rTMS will be administered once a day, 5 days a week. The primary outcome is the Fugl-Meyer assessment of the upper limb. The secondary outcomes include the Arm Subscore of the Motricity Index, Hong Kong edition of Functional Test for the Hemiplegic Upper Extremity, Modified Barthel Index and Modified Ashworth Scale score of the paralysed pectoralis major and biceps brachii. Furthermore, data of diffusion tensor imaging and functional MRI will be collected. These outcomes will be assessed before and after the completion of the intervention.Ethics and dissemination This study has been approved by the Ethics Committee of the First Affiliated Hospital of Nanjing Medical University (2020 SR-266). The findings of this study will be spread through networks of scientists, professionals and the general public as well as peer-reviewed scientific papers and presentations at pertinent conferences.Trial registration number ChiCTR2000038049